Direct and indirect plant regenerations of pineapple var. MD2 (Ananas comosus L.) - Hamid,, N.S.; Bukhori,, M.F.M; Jalil,, M. (Malaysian Society of Applied Biology, 2013)
The variety MD2 of pineapple (Ananas comosus L.) was used in this study. This variety is highly demanded in the international market and known for possessing harvest quality with aroma, high sugar content (14% Brix), vitamins and longer shelf life. However, shortage of planting material has limited the production in Malaysia. In vitro mass propagation using the direct and indirect shoot proliferation techniques was tested on variety MD2. The plantlets were successfully initiated from sucker on solid MS basal medium containing 30 g/L sucrose, 0.1 g/L Myo-inositol and 3 mg/L BAP after one month of culture. The highest direct shoot tips regeneration was obtained on solid MS medium when added with 30 g/L sucrose, 0.1 g/L Myoinositol, 3 mg/L BAP and 1 mg/L NAA. Indirect shoot regeneration was obtained on medium containing 3 mg/L Zeatin after one month of culture. In average, 10 shoots were regenerated from approximately 1 gram of calli. The techniques can produce 100-200 number of plantlet within 4 to 6 months of culture, and ready for planting after 7 months of culture.